Faecal Coliforms (FC) and Faecal Streptococci (FS) Ratio as Tool for Assessment of Water Contamination: A Case Study of River Sokoto, Northwestern Nigeria - M.I.O, Raji; Y.K.E, Ibrahim; B.A, Tytler; J.O, Ehinmidu (The Asia Journal of Applied Microbiology, 2015)
The United States Environmental Protection Agency (USEPA) set limit of 200 faecal coliforms/ 100ml for bacterial contamination of surface water has frequently been exceeded due to agricultural runoff as nonpoint pollution. The study evaluated the effects of cattle rearers and or farmers, and cattle rearing on faecal contamination of water from River Sokoto. Water samples from six designated points on River Sokoto were assessed on monthly basis for faecal coliform and faecal streptococci from January to December, 2014 using faecal coliform/faecal streptococci ratio (FC/FS). The six points studied were namely P1, a point 5 metres away from farmland; P2, a point close to farmland; P3, a point close to residents along the riverside; P4, a point on stream drainage immediately from Sokoto Cement factory; P5, a point on the stream close to the river and P6, a point 5 metres away on the river. Very high mean concentrations of FC and FS were recorded at all sampling points with values exceeding surface water standards of 200 faecal coliform/100ml. While the highest mean FC value of 18,525 MPN/100ml (29.1%) was recorded at P3, the least value of 7,592 MPN/100ml (11.9%) was obtained at P2. Mean FS was recorded highest (2,350 MPN/100ml) at P5 (21.8%) and lowest (625 MPN/100ml) at P4 (5.8%). Mean FC/FS ratios of sampled water P1, P5 and P6 were < 4 (3.78, 3.95 and 3.95 respectively) indicating domestic animal contamination. However, P4 had the highest mean FC/FS ratio > 4 (11.53) indicating human contamination; P2 and P3 also had values > 4 (5.66 and 7.34 respectively) also pointing to human contamination. The FC/FS ratio identified domestic animal contamination sources but did not differentiate between domestic animal and human sources of contamination. Thus the limitatation of its use more as a regulatory tool than a diagnostic tool in identifying contamination sources.